Penyelesaian Tindak Pidana Narkotika Golongan I Yang Mengakibatkan Hilangnya Nyawa Orang Lain - Hartiana, Patrisia Mutia Jersi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This legal writing examines and addresses the Supreme Court of the Republic of Indonesia Decision Number 1644 K/Pid/1988 dated May 15, 1991. In the ratio decidendi of the decision, it is stated that if someone violates customary law and is subsequently subjected to customary sanctions (customary punishment) by the customary leader, that individual cannot be prosecuted again (for the second time) in a state court (District Court) for the same customary law violation and be sentenced to imprisonment under the provisions of the Indonesian Penal Code (Article 5 paragraph (3) sub b of Emergency Law Number 1 of 1951). Based on this background, the issue addressed in this paper is: how does the customary legal system resolve criminal cases? Referring to the aforementioned jurisprudence, in the case of TC, who abused Category 1 narcotics resulting in the death of another person, criminal prosecution should not have proceeded, as the matter had already been resolved through customary law. The approach used by the author is a socio-juridical approach, which emphasizes research intended to empirically understand the law by directly engaging with the object. Socio-juridical research uses secondary data as its initial source, followed by primary data collected from the field or society.